2017
DOI: 10.22159/ajpcr.2017.v10i10.20040
|View full text |Cite
|
Sign up to set email alerts
|

Histological Study on the Protective Effects of Tamarind Seed Extract on Cobra Venom in Mice

Abstract: Objective: Tamarind (Tamarindus indica) has been used as a medical plant for treating many human and animal diseases and widely used as a traditional herbal medicine for the treatment of snake bites. The objective of the study is to investigate whether tamarind seed extract (TSE) has neutralization activity on an adverse histological reaction against venoms of the King Cobra.Methods: A total of 20 healthy mature male mice were randomly divided into 4 groups with 5 mice in each. The control group was injected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This was characterized by dilation of Bowman's space, edema in the cortex and medulla, and congestion and dilation of the distal and proximal tubules. Renal alterations are similar to those observed in Naja nigricollis, Naja Haje, and Ophiophagus hannah venoms have been reported, which induce morphological changes in the renal glomeruli resulting in complete lysis of renal corpuscles with rupture of Bowman capsules and acute tubular necrosis [39,42]. These renal abnormalities can be attributed to the higher absorption of the venom in the kidneys of the animals, as previously demonstrated with Naja nigricollis venom leading to renal abnormalities.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This was characterized by dilation of Bowman's space, edema in the cortex and medulla, and congestion and dilation of the distal and proximal tubules. Renal alterations are similar to those observed in Naja nigricollis, Naja Haje, and Ophiophagus hannah venoms have been reported, which induce morphological changes in the renal glomeruli resulting in complete lysis of renal corpuscles with rupture of Bowman capsules and acute tubular necrosis [39,42]. These renal abnormalities can be attributed to the higher absorption of the venom in the kidneys of the animals, as previously demonstrated with Naja nigricollis venom leading to renal abnormalities.…”
Section: Discussionsupporting
confidence: 74%
“…Microscopic analysis of the livers of mice envenomed mice revealed alterations in liver tissue characterized by ballooning and cytoplasmic vacuolation of hepatocytes and dilation of the sinusoidal vessel. Studies have reported envenomation with Naja naja [ 36 ], the royal coba Ophiophagus hannah [ 42 ], and Walterinnesia aegyptia [ 43 ]. According to the results of Tohamy and coworkers’ study [ 44 ], the effect of PLA 2 from the venom Naja haje could be among the factors responsible for the rupture of liver cell membranes, as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%